2007
DOI: 10.1007/s00417-007-0704-4
|View full text |Cite
|
Sign up to set email alerts
|

Circadian changes of intraocular pressure and ocular perfusion pressure after timolol or latanoprost in Caucasians with normal-tension glaucoma

Abstract: Latanoprost induces an IOP reduction greater than timolol, also achieving a better circadian flattening of the IOP curve. Only latanoprost significantly increased mean 24-hour OPP. The management of Caucasian NTG patients should be critically realized, considering the 24-hour influence of each IOP-lowering drug on the ocular blood perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
(67 reference statements)
3
28
0
Order By: Relevance
“…Previous reports on ophthalmic timolol suggest its effects on blood pressure and heart rate in spite of low plasma concentration [12][13][14] mainly during night time. It is contraindicated in patients with bronchial asthma, severe chronic obstructive pulmonary disease, and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports on ophthalmic timolol suggest its effects on blood pressure and heart rate in spite of low plasma concentration [12][13][14] mainly during night time. It is contraindicated in patients with bronchial asthma, severe chronic obstructive pulmonary disease, and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 97%
“…7,8) Although some clinical trials have reported that topical PGF2α analogs are safe, [9][10][11] they are thought to cause systemic adverse events. Some examples include ophthalmic timolol or brimonidine, which reduce systemic blood pressure by β-receptor blocking [12][13][14] or α-receptor stimulating actions. 15) It would be difficult to demonstrate the relationship using an epidemiologic study, since the systemic drug adverse events caused by eye drops are very rare.…”
mentioning
confidence: 99%
“…In a crossover study of 60 eyes of 30 newly diagnosed NTG patients, Costagliola et al 21 investigated the influence of latanoprost 0.005% and timolol 0.5% on 24-hour sitting IOP, BP, and MOPP (calculated as 2/3MAP --IOP). Although both medications significantly reduced mean circadian IOP compared to baseline, there was a difference of 1.3 mm Hg in favor of latanoprost.…”
Section: The Effect Of Topical Medications On Opp Rhythmmentioning
confidence: 99%
“…[25][26][27] Among the topical antiglaucoma eye drops, the prostaglandin F2-alpha analogs (travoprost, latanoprost, and bimatoprost) and dorzolamide increase OPP, whereas timolol, a beta-blocker, and brimonidine do not. [28][29][30] Therefore, to investigate the effect of eye drops, both the reduction in IOP and the hemodynamic effects of the medication should be evaluated.…”
Section: Discussionmentioning
confidence: 99%